Political and Religious Impacts on COVID-19 Responses in Tanzanian Healthcare Facilities: A Qualitative Cross-Sectional Survey - Magwe, Edward Augustine (AlQalam Journal of Medical and Applied Sciences, 2024)
Coronavirus disease (COVID-19), a virus-related illness that affects the respiratory system, first appeared in Wuhan province, China, in December 2019. By mid-January 2020, cases of COVID-19 were reported in numerous Asian countries, signaling the beginning of a global health crisis. Within a mere four months, the virus had spread to all continents. A qualitative cross-sectional survey was conducted from 24 August to 3 October 2022 among healthcare workers in the Dar es Salaam, Arusha, Dodoma, and Mwanza regions. A total of 96 participants were involved from 24 healthcare facilities in all four regions. Individual interviews and key informant interviews were recorded using the Kobo Toolbox and analyzed thematically. The study revealed that many participants felt that politics misled society rather than educating. The way healthcare workers in Tanzania expressed their views on the impacts of politics in fighting the outbreak of COVID-19 was found to threaten the safety of healthcare workers and general public health. A significant number of healthcare workers also expressed that religion hurt the fight against COVID-19 in their facilities and the general society. However, A few health workers believed that religion had a positive influence, while others felt that it had advantages and disadvantages depending on its application. In Tanzania, politics and religion misled the community to a large extent rather than educating it. Clean politics and good religious practices should be used when fighting pandemics such as COVID-19. ظهر مرض فيروس كورونا (كوفيد-19)، وهو مرض مرتبط بالفيروس يؤثر على الجهاز التنفسي، لأول مرة في مقاطعة ووهان بالصين في ديسمبر 2019. وبحلول منتصف يناير 2020، تم الإبلاغ عن حالات إصابة بكوفيد-19 في العديد من البلدان الآسيوية، مما يشير إلى بداية أزمة صحية عالمية. وفي غضون أربعة أشهر فقط، انتشر الفيروس إلى جميع القارات. وأُجري مسح مقطعي نوعي من 24 أغسطس إلى 3 أكتوبر 2022 بين العاملين في مجال الرعاية الصحية في مناطق دار السلام وأروشا ودودوما وموانزا. وشارك ما مجموعه 96 مشاركًا من 24 منشأة رعاية صحية في جميع المناطق الأربع. وتم تسجيل المقابلات الفردية ومقابلات المخبرين الرئيسيين باستخدام Kobo Toolbox وتحليلها موضوعيًا. وكشفت الدراسة أن العديد من المشاركين شعروا بأن السياسة ضلل المجتمع بدلاً من تثقيفه. تبين أن الطريقة التي عبر بها العاملون في مجال الرعاية الصحية في تنزانيا عن آرائهم بشأن تأثيرات السياسة في مكافحة تفشي كوفيد-19 تهدد سلامة العاملين في مجال الرعاية الصحية والصحة العامة. كما أعرب عدد كبير من العاملين في مجال الرعاية الصحية عن أن الدين أضر بمكافحة كوفيد-19 في مرافقهم والمجتمع بشكل عام. ومع ذلك، يعتقد عدد قليل من العاملين في مجال الصحة أن الدين له تأثير إيجابي، بينما شعر آخرون أنه له مزايا وعيوب اعتمادًا على تطبيقه. في تنزانيا، ضلل السياسة والدين المجتمع إلى حد كبير بدلاً من تثقيفه. يجب استخدام السياسة النظيفة والممارسات الدينية الجيدة عند مكافحة الأوبئة مثل كوفيد-19